Managing at the speed of change - Schroeder, Don; Winter, Kris; Edwards, Lee; Conner, Daryl narration (United States : Mentor Media [production company] Sydney : First Training [distributor])
This story is about the change of the new technology to people's life. How the new innovations in technology can effect social life.
Sound, Ernest Shinegawa ; music, David Siebels, director of photography, Stuart Asbjornsen
Keywords: Technological innovations -- Social aspects -- United States